(untitled) (Journal of the Society for Musicology in Ireland, 2021)
A review of Ludwig van Beethoven: Symphonies 1–3; Gerald Barry: Beethoven, Piano Concerto, Nicolas Hodges, Mark Stone, Britten Sinfonia conducted by Thomas Adès, Signum Classics (2020), (CD) SIGCD616. Ludwig van Beethoven: Symphonies 4–6; Gerald Barry: Viola Concerto, The Conquest of Ireland, Lawrence Power, Joshua Bloom, Britten Sinfonia conducted by Thomas Adès, Signum Classics (2020), (CD) SIGCD639. Ludwig van Beethoven: Symphonies 7–9; Gerald Barry: The Eternal Recurrence, Jennifer France, Christianne Stotjin, Ed Lyon, Matthew Rose, Britten Sinfonia conducted by Thomas Adès, Signum Classics (2021), (CD) SIGCD659.